Frontier heartland : analysing the impact of forestry and tourism on 'white' identity in Maclear - Griffin, Donna-Lee (Rhodes University, Faculty of Humanities, Department of Anthropology, 2006)
The North Eastern Cape in South Africa is part of a larger province that is in desperate need of job creation and economic development. In light of these needs, efforts have been made by members of the community and outside investors to generate new forms of income in the area. These economic developments emerged in the form of small-scale tourism initiatives and commercial forestry. The impact of these developments on the small community of Maclear differs in nature and is bringing about social change and influencing identity. In this thesis, I explore the effects of each of these developments on the local farming community, particularly the established white English-speaking farmers. For various important reasons, such as the changes to land use patterns occurring around them in terms of forestry and tourism initiatives, I chose to examine the situation of this minority. In general discussions and portrayals of white farmers, it is hypothesized that whites living in small farming communities are resistant to change, politically stagnant and socially conservative. In this thesis I test this hypothesis and investigate what South Africans might see as the core, or whether there is a core of, white settler identity. TIle idea of 'frontiers' being heartlands was emphasized in Maclear as residents spoke about the pioneering efforts of their forefathers and discussed these efforts as the essence of their identity. Forestry is a contemporary ' frontier' encroaching on these white Settlers. A dynamic concept of landscape is central to these identity construction efforts. In this thesis I explore, through different articulations of landscape, how residents, recent arrivals and investors attempt to embed their identity and resources in the community. I ask whether it is possible for members of the white community to produce an alternate and politically viable interpretation of landscape in post-apartheid South Africa. Can land and landscape offer them a sense of belonging and identity? What is their experience in view of the impositions of major investors who see land purely as an economic unit? The research does not explicitly investigate how 'new' black farmers and farming groups perceive and experience land and landscape. What is noted is the imagined passivity of black labourers on white-owned land. This thesis touches on issues inlportant to democratic change and progress in South Africa. How will the new government deal with the thorny issue of land redistribution in the face of competing claims for land and identity? How will the various sections of the white community (in this case the farming community) negotiate their identity in the new South Africa? Also, what do ' frontier' towns like Maclear reveal about the nature of white identity in post-apartheid South Africa? This thesis relies on gender and constructionist theories of landscape as developed by Appadurai (1996) to explain the dynamic nature of landscape in Maclear. It also explores and appraises the idea of ' frontier'. In the analysis of identity, I take into account that white settlers 'success' relies in part on the settlers ability to adapt to the ' frontier' and their ability to construct a new identity in their newfound 'homeland' (simliar to Paul Gilroy's (1993) "double consciousness). Keywords: South Africa, Maclear, Farming, White Identity, Landscape and Tourism.
Keywords: Agriculture -- South Africa -- Maclear; Agriculture -- Economic aspects -- South Africa -- Maclear; Economic development -- South Africa -- Maclear; Tourism management -- South Africa -- Maclear; Forests and forestry -- Economic aspects -- South Africa -- Maclear; Whites -- South Africa -- Maclear -- Economic conditions